Cultural appropriateness of care delivery - Pinedo, Adolfo (2015)
The maternal mortality rate in Peru for the past 20 years has not had a major change: 300 per 100 000 live births to 261 per 100 000 live births. The causes of this high maternal mortality are several. One is the minimal access of women giving birth at health facilities, especially in the provinces of the Andean Trapezoid, which determines institutional delivery coverage in these areas below the national average, which is around 55%, which also low compared to other countries in the region.